Visualising skyscapes
1 online resource.
Keywords: "Above the land and its horizon lies the celestial sphere, that great dome of the sky which governs light and darkness, critical to life itself, yet its influence is often neglected in the archaeological narrative. Visualising Skyscapes captures a growing interest in the emerging field of skyscape archaeology. This powerful and innovative book returns the sky to its rightful place as a central consideration in archaeological thought and can be regarded as a handbook for further research. Bookended by a foreword by archaeologist Gabriel Cooney and an afterword by astronomer Andrew Newsam, its contents have a wide-reaching relevance for the fields of archaeology, anthropology, ethnography, archaeoastronomy, astronomy, heritage and cultural studies. The volume balances six chapters on theory and methodology which elaborate on the history and practice of the field with six other chapters focused on case studies from around the world. As such it captures the growing interest in the multidisciplinary study of skyscapes and will be of interest to academics, students and the general public, as well as having international appeal. It is topical, timely and relevant to current debates and will hopefully stimulate further interest in this exciting and relatively new area of investigation. The contributions showcase the work of distinguished academics in the field and the chapters are all enhanced by colour photographs and images"--